The awareness of hibah as a tool to reduce estate planning risk among the Sekolah Kebangsaan Taman Nirwana (SKTN) teacher and staff, Ampang - Ashari, Hudzaifah; Amir, Nur Aisyah Suzelan (2013)
The topic of this research is “A Study on the Awareness of Hibah as a Tool to reduce Estate Planning risk among the teacher and staff at Sekolah Kebangsaan Taman Nirwana. Managing one’s assets are important and managing on how the assets should be delegate to heirs is not something trivial and simple. It is clearly proven in Malaysia through various situations such as dispute of assets among heirs or assets are frozen due to non-existent of any plan which ends up causing problem to the family members in Islam. Muslims are urged to have a proper planning of their property. Muslims are not only tied to the law of faraid in managing their assets as there are other techniques which are permissible to be exercise such as hibah. Therefore, this research aims on finding the level of awareness among teacher and staff at Sekolah Kebangsaan Taman Nirwana on hibah as a tool to reduce estate planning risk. Also, to determine the greatest factor that influence awareness on hibah while at the same time to determine the relationship between knowledge, attitude and promotion on awareness towards hibah to reduce estate planning risk. From the result it was found that the respondents possess high level of awareness towards hibah as tool to reduce estate planning risk. Also, it shows that only knowledge and promotion have significant relationship on awareness while knowledge is the greatest factor influencing awareness on hibah.